Ion charge-resolved branching in decay of inner shell holes in Xe up to 1200 eV. (4th September 2015) - Eland, J H D; Slater, C; Zagorodskikh, S; Singh, R; Andersson, J; Hult-Roos, A; Lauer, A; Squibb, R J; Feifel, R
Abstract: Using a new multi-electron multi-ion coincidence apparatus and soft x-ray synchrotron radiation we have determined branching ratios to final Xe n+ states with 2 <  n  < 9 from the 4d −1, 4p −1, 4s −1, 3d −1 and 3p −1 Xe + hole states. The coincident electron spectra give information on the Auger cascade pathways. We show that by judicious choice of coincident electrons, almost pure single charge states of the final ions can be selected.